Layered Closure of Lumbosacral Myelomeningocele Defects with Bilateral Paraspinous Muscle and Composite Fasciocutaneous Flaps. Issue 6 (June 2020) - Holoyda, Kathleen A.; Kim, Erinn N.; Tuncer, Fatma B.; Maglic, Dino; Hosein, Ray C.; Kestle, John R.; Siddiqi, Faizi A.; Gociman, Barbu R.
Abstract : Summary: Robust, reliable, and reproducible closure of lumbosacral myelomeningocele defects remains a challenge. In infants with lumbosacral myelomeningocele defects, multiple methods of soft tissue coverage have been described. These include various cutaneous, fascial, and muscle flaps and grafts. This is done with relative ease when ample soft tissue is present but becomes extremely difficult for large and distally located defects. We present here our closure technique of lumbosacral myelomeningocele defects in newborns, with associated short- and medium-term outcomes. We demonstrate the anatomy of this technique with fresh cadaver dissection and present a review of demographic and outcome data of 12 consecutive patients treated with this method from June 2014 to August 2019. No major intra- or postoperative complications have been encountered, with a mean follow-up of 22.2 months and median follow up of 18 months. After the neurosurgical repair of lumbosacral myelomeningocele, bilateral composite fascial flaps composed of thoracolumbar and gluteus maximus fascia are elevated in continuity. The paraspinous muscle flaps are then elevated, disinserted distally, and medialized to provide complete muscular coverage of the dural repair. The bilateral composite fascial flaps are medialized and closed over the deep paraspinous muscle flap repair. Two patients experienced areas of small, superficial skin necrosis, one of which healed by secondary intention and the other by debridement and full-thickness skin grafting. Use of bilateral paraspinous muscle flaps and bilateral composite fascial flaps composed of thoracolumbar and gluteus maximus fascia provides robust coverage of lumbosacral defects following myelomeningocele repair in infants. Abstract : Supplemental Digital Content is available in the text.